Writing in a Foreign Language: The Rhetorical and Argument Styles in Research Article Drafts by Nonnative Speakers of English in Linguistics and Language Education - Arsyad, Safnil; Nur, Sahril; Nasihin, Ahmat; Syahrial, Syahrial; Adnan, Zifirdaus (Universitas Negeri Makassar, 2021)
Unlike for lecturers in Engineering, Medicine, Computer Science, and Agriculture and Biology Sciences, for Indonesian lecturers in Social Sciences and Humanities including in Linguistics and Language Education (LLE), publishing research articles in reputable or indexed international journals is very difficult. The possible cause of the difficulty is their unfamiliarity with the correct and appropriate use of rhetorical style in their articles as expected by international journal readers. This study is aimed at investigating the rhetorical of research article (RA) drafts written in English by Indonesian lecturers in Applied Linguistic and English Language Education in five different universities in Indonesia (i.e., Bengkulu University, Padang State University, Atmajaya Catholic University, Mataram University, and Makassar State University). A corpus of 20 English RA drafts was analyzed on their rhetorical and linguistic quality using a genre-based method. The results show that the majority of the RA drafts have addressed important moves in each section of the articles but in terms of the argument quality still needs improvement. This implies that the Indonesian university lecturers in LLE need to be familiar with and able to argue well in their article drafts as it is expected by international readers.Â